Analysts and stock liquidity: Global evidence - Dang Tùng Lâm; Nguyen Trang Phuong Doan; Thi Minh Hue Nguyen; Thanh Thao Tran; Xuan Vinh Vo (Cogent Economics & Finance, 2019)
This paper investigates the relation between analyst coverage and stock liquidity with a focus on the role of information produced by financial analysts. Using a comprehensive dataset across 41 countries for the period 2000-2010, we document two novel findings. First, analyst coverage is positively correlated with stock liquidity. Second, the positive effect of analyst following on stock liquidity is attributed to the weak institutional environment. These findings suggest that financial analysts provide more public information to market participants and thus improve stock liquidity. This effect is attenuated in a country with a stronger institutional environment.
Keywords: 330; Analyst coverage; stock liquidity